PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP BUYING DECISION PRODUK SOMETHINC DI POLITEKNIK NEGERI UJUNG PANDANG - Tandiallo, Millenia Viska; Jayadi, Jayadi; Utami, Dian Gita (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2024)
This study aims to determine the influence of e-wom and brand image on buying decisions of Somethinc at Politeknik Negeri Ujung Pandang. The sampling technique used purposive sampling with total of 98 respondents. The data analysis used descriptive statistical analysis using IBM SPSS 25 where the tests used were validity and reliability tests, and classical assumption tests. The hypothesis in this study is associative hypothesis where the tests used are multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results of this study: (1) e-wom has positive and significant effect on buying decisions with a sig. value of e-wom 0,003 < 0.05 and a t-value of 3,106 > greater than the t-table value of 1,985. (2) brand image has positive and significant effect on buying decisions with a sig. value of brand image of 0,000 < 0,05 and a t-value of 3,811 > greater than the t-table value of 1,985. (3) e-wom and brand image simultaneously have positive and significant effect on buying decisions with significance level of 0,000 < 0,05 and an F-value of 48,345 greater than the F-table value of 3,092 and the R2 value of e-wom and brand image on buying decisions is 50.4%.